Peranan Badan Narkotika Nasional (BNN) Dalam Upaya Pencegahan Terhadap Tindak Pidana Narkotika - Ida Bagus Trisnha Setiaawan; Ida Ayu Putu Widiati; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2020)
Abstract—Narcotics is a substance that can make anyone who consumes it lose consciousness and various adverse effects can be caused from this drug because it contains both centric and semi-sentimental plants that affect brain performance until the disappearance of the pain that is felt but makes severe dependence, as for types and various types and this class of drugs has been attached to this Act. The formulation of the problem in this paper is how the duties and authority of the National Narcotics Agency in the act of criminal narcotics and what are the efforts of the National Narcotics Agency in the prevention of narcotics crimes. The research method used in this research is normative legal research; the author uses the main approach, namely the legislative approach to narcotics crime. By the National Narcotics Agency and enforcement practices and constraints that occur in eradicating narcotics crime faced by the National Narcotics Agency, the source of the author's legal material is obtained from a literature study of primary legal material and secondary legal material. The National Narcotics Agency is a non-ministerial government institution domiciled under the President and responsible to the President. The National Narcotics Agency has the duty and authority in the field of prevention and eradication and abuse of narcotics. The National Narcotics Agency encountered several obstacles in carrying out its duties, which were not sufficient operational costs, inadequate facilities and infrastructure, and a lack of community participation in helping the National Narcotics Agency to prevent narcotics crime .